2017
DOI: 10.19044/esj.2017.v13n19p70
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Professional Self-Confidence: Opinions of Lithuanian, Ukrainian and Finnish Teachers

Abstract: The current study reports findings of quantitative investigation of the opinions of Lithuanian, Ukrainian and Finnish teachers on their perceived professional self-confidence with a sample of 393 practicing teachers. Teachers' self-esteem, self-and collective efficacy were examined as components of teachers' professional self-confidence. Collective efficacy beliefs were measured in terms of teachers' subjective perception of efficacy of school community members, namely, the principal, colleagues, students and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Confidence generally arises when a person will engage in or engages in a particular activity in which his mind is directed towards achieving a desired outcome (Ertmer and Ottenbreit-Leftwich, 2010). From the developmental dimension, self-confidence can grow healthily when there is recognition from the environment (Ponomarenko, 2017). Based on the above definition, it can be concluded that selfconfidence is a positive attitude possessed by an individual who acclimates and enables him to develop a positive assessment.…”
Section: The Nature Of Confidencementioning
confidence: 99%
“…Confidence generally arises when a person will engage in or engages in a particular activity in which his mind is directed towards achieving a desired outcome (Ertmer and Ottenbreit-Leftwich, 2010). From the developmental dimension, self-confidence can grow healthily when there is recognition from the environment (Ponomarenko, 2017). Based on the above definition, it can be concluded that selfconfidence is a positive attitude possessed by an individual who acclimates and enables him to develop a positive assessment.…”
Section: The Nature Of Confidencementioning
confidence: 99%